Investigation of Galactic Supernova Remnants and their Environment in 26.°6 < l < 30.°6, ∣b∣ ≤ 1.°25 Using Radio Surveys - Luo, Tian-Xian; Zhou, Ping; He, Hao-Ning (The Astronomical journal, 2024)
The problem of missing Galactic supernova remnants (SNRs) refers to the issue that the currently known Galactic SNRs are significantly incomplete compared to the theoretical prediction. To expand the sample of Galactic SNRs, we use GLEAM and THOR+VGPS data across four wave bands ranging from 118 to 1420 MHz to drive a spectral index map covering the region within 26.°6 < l < 30.°6, ∣ b ∣ ≤ 1.°25, where numerous SNR candidates were recently found. By using the spectral index map of the sky region and detailed analysis of the spectral indices of individual sources, we confirmed four SNR candidates, namely G26.75+0.73, G27.06+0.04, G28.36+0.21, and G28.78−0.44, as SNRs. Additionally, we discovered an expanding molecular superbubble located in this region, discussed pulsars associated with SNR candidates, and discovered a long H α filament that spatially overlaps with the candidate G29.38+0.10. We suggest that the problem of missing Galactic SNRs not only arises from observation limitations, but also could be due to the low-density environments of some SNRs, and the different supernova explosion properties.